Demanding Diagnosis of Splenic Angiosarcoma as Cause of Delayed Treatment of Spontaneous Splenic Rupture: A Case Report and Literature Review. (2nd February 2017) - Coppola, Sara; Leva, Andrea; Pagni, Fabio; Famularo, Simone; Gianotti, Luca
Abstract : Background. Primary splenic angiosarcoma is a very rare mesenchymal malignant tumor associated with a poor prognosis due to its high metastatic potential. This disease can be easily neglected and spontaneous splenic rupture is a frequent manifestation at the time of diagnosis leading to a poor outcome because of peritoneal dissemination. Case Presentation. We describe the case of a 49-year-old man who presented with asthenia, left upper quadrant abdominal pain, and anemia. Computerized tomography scan showed an enlarged spleen with no nodules and a nontraumatic rupture of the splenic capsule. Splenectomy was performed on account of the severe anemia and histopathology examination showed a primary angiosarcoma. Conclusions. Splenic angiosarcoma should be considered as one of the differential diagnoses in patients with nontraumatic spleen rupture and a specific previous medical history. Regrettably, splenectomy allows for a definitive diagnosis but not a curative treatment.